From efficacy to effectiveness: insecticide-treated bednets in Africa. - Lengeler, C; Snow, R (1996)
Insecticide-treated bednets and curtains (ITBC) have proven in recent large-scale trials to have a high efficacy in reducing morbidity and mortality from malaria in African children. However, it is unlikely that the efficacy measured in trials can be entirely sustained under programme conditions. This has important implications for the cost-effectiveness of the intervention. Furthermore, there is a need to assess the long-term impact of ITBC. This article traces the history of ITBC and the different phases of their assessment, especially the determination of efficacy in randomized controlled trials (phase III assessment). It then outlines the reasons for continued assessment of their effectiveness under programme conditions (phase IV assessment). The methodologies for measuring effectiveness are discussed, and a critical review of the issues reveals that it is impractical to measure effectiveness directly. A simple effectiveness model, allowing for differentiation between individual and community effectiveness, provides a useful conceptual framework. First, individual effectiveness is measured through a case-control study. This estimate is then combined with a coverage indicator to estimate community effectiveness. This approach could provide programme managers with a powerful tool to monitor the impact of health interventions at the community level.